Key factors for Startups in Colombia and emerging economies (2024)
This research seeks to identify the factors that influence the creation of Startups with high growth potential in a developing economy. A qualitative approach with an exploratory-descriptive scope was followed, conducting 25 semi-structured interviews with members of entrepreneurship units in the city of Medellín, Colombia. The results indicate that the internal factors that most influence the creation of Startups with growth potential are: the profile of the entrepreneur, his work team and knowledge of the market. External factors correspond to economic aspects and capacity of the entrepreneurship ecosystem, such as: financial leverage, risk capital, financing, loans and calls. It concludes with the need for venture capital financing, specialized advice, and effective collaboration between universities, companies and the State to promote the strengthening of startups and contribute to the economic development of the country.